SIMILARITAS KONSEP PEMIKIRAN THOMAS AQUINAS DALAM PANDANGAN FILSAFAT JAWA SERAT WIRID HIDAYAT JATI - Mohamad Makincoiri; Afendy Widayat; Agatia Mega Rianda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2025)
This article discusses the Thomism concept of thought initiated by Thomas Aquinas and the divinity views contained in Serat Wirid Hidayat Jati by Raden Ngabehi Ronggowarsito as well as the interference of the beliefs or religions held by Thomas Aquinas and Raden Ngabehi Ronggowarsito. The aim of writing this article is to find out the similarities between the divinity and cosmological concepts of Thomas Aquinas and the concept of divinity in Serat Wirid Hidayat Jati by Raden Ngabehi Ronggowarsito and the theological views of both. The research method in this study is the literature study method. The result of this research is the finding of similarities between the thoughts of Thomas Aquinas and Ronggowarsito as outlined in Serat Wirid Hidayat Jati and the influence of religion in the perspectives of Thomas Aquinas and Raden Ngabehi Ronggowarsito. The similarities are in the existence of God, the oneness of God, cosmological arguments and the creation theory of the universe. The religious influence that interferes in Thomas Aqinas' view is Christianity, while in Raden Ngabehi Ronggowarsito's view is Islam.